Particularización de un modelo de medición del grado de madurez organizacional en gerencia de proyectos para empresas de transmisión de energía eléctrica en Colombia (2018)
This document presents the particularization of an organizational project management maturity model for electricity transmission companies in Colombia, taking into account that more than 79% of transmission projects in the country end out of time or are canceled and that, as indicated by the Japan Project Management Association, through Toshiharu Watanabe, "... although there are global, regional and industry-specific project management standards, these must be particularized depending on the situation and the context…". For this, the literature review is carried out, to characterize the sector studied and identify existing maturity models that serve as reference. Additionally, to know the particularities of the sector within the framework of project management, interviews are conducted with experts from the sector, presenting the main results. Once the sector has been characterized, the reference maturity models have been defined and the particularities have been known, we development the model M³OGP-ETEEC, defining the scope, the maturity levels, the evaluation areas, the evaluation form and the question bank. Finally, a Web application is built as the tool to measure the organizational maturity of each one of the evaluation areas of the M³OGP-ETEEC model.